The effects of whey and soy proteins on growth performance, gastrointestinal digestion, and selected physiological responses in rats. Issue 3 (8th February 2018) - Wróblewska, B.; Juśkiewicz, J.; Kroplewski, B.; Jurgoński, A.; Wasilewska, E.; Złotkowska, D.; Markiewicz, L.
Abstract : The objective of this work was to identify the nutritional and physiological effects of commercial soy and whey protein preparations. Abstract : The objective of this work was to identify the nutritional and physiological effects of commercial soy and whey protein preparations. Wistar rats were fed with soy (S), whey (W), or casein (C) preparations as the sole dietary protein source. The nitrogen balance, body composition, changes in caecal microbiota, mucosal and bacterial enzyme activities, and allergenic potential of the preparations were analysed. The whey diet elicited greater skeletal muscle anabolism than the soy diet. Rats from the S group had the lowest values of body weight, fat, and lean mass gain. Compared to casein, soy and whey preparations decreased the protein efficiency ratio, increased N in the urine, and triggered the reduction of ammonia levels in the caecum. Changes in β-glucuronidase and β-galactosidase activities in the small intestine, caecum, and colon between experimental groups were observed. Significant differences were noted in the total counts of anaerobic bacteria and sulphite reducing bacteria during soy and whey treatments. This probably affected the short chain fatty acid level in caecal digesta resulting in the lowest propionic acid and total putrefactive short chain fatty acid levels during S treatment. Generally, whey preparations are a good choice for rapid bodybuilding (skeletal muscles), whereas soy preparations are more helpful during mass reduction.